Peso regionais na funç\~ao de bem-estar social: Uma aplicaç\~ao para o Fundo de Participaç\~ao dos Estados (FPE) - Roberta da Silva Vieira; Leonardo M. Monasterio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Using the tools of Welfare Economics, the study estimates states' weights in the social welfare function of contemporary Brazil. Based on PNAD 2009 microdata, two methods of calculating the weights were applied: the Equally Distributed Equivalent Income (EDEI) and the average marginal utilities (AMU). The weights were calculated for a range of values of 'e', the coefficient of inequality aversion. When 'e' equals 1.43, the regional weights ranged from 0.44 for Santa Catarina to 2.55 for Alagoas (EDEI method). Finally, the paper presents the results of the regional weights technique on the Fundo de Participaç\~ao dos Estados (States' Participation Fund) taking into account the income inequalities between and within states.
Keywords: H75; D63; H77; 330